Care and Service at Home for Persons With Dementia in Europe. Issue 5 (7th August 2015) - Bökberg, Christina; Ahlström, Gerd; Leino‐Kilpi, Helena; Soto‐Martin, Maria E.; Cabrera, Esther; Verbeek, Hilde; Saks, Kai; Stephan, Astrid; Sutcliffe, Caroline; Karlsson, Staffan
Abstract: Purpose: To describe available and utilized formal care and service at home for persons with dementia, from diagnosis to end‐of‐life stage, in eight European countries. Design: A descriptive cross‐country design concerning eight European countries as a part of the European research project RightTimePlaceCare. Methods: The research team in each country used a mapping system to collect country‐specific information concerning dementia care and service system. The mapping system consists of 50 types of care and service activities. Sixteen of the 50 predefined activities concerning care and service at home were selected for this study and subdivided into three categories, following the stages of dementia. Findings: Availability was reported to be higher than utilization, and the findings indicated more similarities than differences among the eight countries involved. Even though there were several available activities of "basic care and services" and "healthcare interventions, " they were utilized by few in most countries. Furthermore, "specialized dementia care and services" were sparsely available and even more sparsely utilized in the participating countries. Conclusions: The findings indicated that persons with dementia in Europe received formal care and service on a general, basic level but seldom adjusted to their specific needs. Clinical Relevance: This study describes the gap between service provision and utilization enabling nurses to develop individually adjusted care plans for persons with dementia during the progress of the disease. The findings do not include matters of quality of care or how to best organize effective care and services. However, the activities of care and services presented here should shed light on what room there is for improvement when it comes to enabling persons with dementia to go on living at home.